2021
DOI: 10.1016/j.ijid.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and medical care factors associated with mortality in French nursing homes during the COVID-19 outbreak

Abstract: Highlights Among nursing homes with COVID-19 cases, mortality rates are highly variable. Hospital dependent nursing homes are associated with lower mortality rates. Increased material, human and medical resources reduce mortality in nursing homes. Daily clinical examination by a physician reduces mortality in COVID-19 nursing home patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…36 It has also been hypothesized that malnutrition could be an important risk factor, 37,38 but we did not find an association between food intake and mortality after adjustment for other risk factors, as in a previous study. 18 However, there was a trend toward an increased risk of mortality in those with the lowest BMI. Although this did not reach statistical significance, likely because of the small number of people in that BMI category, it cannot be ruled out that underweight is a risk factor for COVID-19 mortality in LTCF residents.…”
Section: Discussionmentioning
confidence: 96%
“…36 It has also been hypothesized that malnutrition could be an important risk factor, 37,38 but we did not find an association between food intake and mortality after adjustment for other risk factors, as in a previous study. 18 However, there was a trend toward an increased risk of mortality in those with the lowest BMI. Although this did not reach statistical significance, likely because of the small number of people in that BMI category, it cannot be ruled out that underweight is a risk factor for COVID-19 mortality in LTCF residents.…”
Section: Discussionmentioning
confidence: 96%
“…The coordination between NH, primary care, and hospital care has been key during the pandemic. A study carried out in France in three nursing homes highlights that those nursing homes that received support from the hospital had lower mortality [25] Furthermore, after the first wave, this new form of work and collaboration has served to implement worldwide new strategies with to improve the care of the older persons living in, such as the formation of liaison geriatric hospital-based team units in our region [9].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the fatality rate was very high in the early outbreak countries, as was it high in early period in China [26] . In France, for example, it was reported that in the rst three months of the epidemic, due to lack of validated COVID-19 treatment, the fatality rate in some medical institutions reached up to 44% [27] .…”
Section: Discussionmentioning
confidence: 99%